Working Together Pays Dividends for Official Language Minority Communities! - Quebec English-language Production Council; Quebec Community Groups Network (QCGN); English Language Arts Network (ELAN); Alliance nationale de l'industrie musicale; Alliance des producteurs francophones du Canada (APFC); Fédération culturelle canadienne-française (FCCF) (2022)

What is the Difference Between a Common and Official Language? - Quebec Community Groups Network (QCGN) (2023)

What Exactly is the Notwithstanding Clause, and Why Does it Matter? - Quebec Community Groups Network (QCGN) (2021)

What Are Your Rights When Under Arrest? - Quebec Community Groups Network (QCGN) (2020)

Vindicated by Court of Appeal Victory, QCGN Recommends Quebec Government Renounce Upheaval of English School Boards - Quebec Community Groups Network (QCGN) (2020)
Keywords: Official Language Minority Community (OLMC)

Use of Notwithstanding Clause Would Run Roughshod Over Rights of English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2021)

Use of French in Federally Regulated Private Businesses Act Abandons English-speaking Quebecers, QCGN Tells Senate Committee - Quebec Community Groups Network (QCGN) (2022)

Un sondage révèle que les Québécois d’expression française appuient fermement le droit des citoyens d’expression anglaise d'obtenir des services gouvernementaux en anglais - Quebec Community Groups Network (QCGN) (2022)

Un réglement adopté en catimini pourrait nuire à la qualité des soins de santé des Québécois d'expression anglaise - Quebec Community Groups Network (QCGN) (2022)

Un régime de droits linguistque pour les entreprises de compétence fédérale? - Quebec Community Groups Network (QCGN) (2023)

Un comité de la Chambre des communes vote pour l’abandon des Québécoises et des Québécois d’expression anglaise - Quebec Community Groups Network (QCGN) (2023)

Tuition hikes : Government chooses path that could ruin Quebec’s English universities - Quebec Community Groups Network (QCGN) (2023)

True Impact of Bill 96 on English-speaking Community Now Abundantly Clear - Quebec Community Groups Network (QCGN) (2021)

Tradition Allows MNA Coiteux to Speak English in National Assembly - Quebec Community Groups Network (QCGN) (2017)

Thousands of Quebecers Sign Petitions Seeking Changes to Bill 10 - Quebec Community Groups Network (QCGN) (2014)

The Official Languages Act and the English-speaking Community of Quebec : Looking to the Future - Johnston, Nicola (2010)
Remarks to the Standing Committee on Official Languages

The Official Languages Act and the English-speaking Community of Quebec : Learning from the Past - Donnelly, Robert (2010)
Keywords: Official Language Minority Community (OLMC)

The Constitution and the English Language in Quebec : Education ; the Primacy of the French Language ; Collective Rights - Bergman, Michael N.; Daniels, Katarina (Quebec Community Groups Network (QCGN))
Soon after its Spring 2014 election victory, the new government announced a series of austerity measures designed to meet an election promise of a balanced budget by the end of the following fiscal year. Institution by institution was hit with news of budget cuts over the course of the following months, and in November 2014, the Education Minister announced his plan to “slash 50 per cent of school boards,” as one media outlet reported it. 1 According to the government, centralization of school boards would put “millions” back into provincial coffers without affecting the quality of education offered by the school boards; the Education Minister would see the number of French school boards drop from 60 to 36, and the number of English ones drop from 9 to 7.

Suggesting Change : The Situation of the English-speaking Minority of Quebec and Proposals for Change - Quebec Community Groups Network (QCGN) (2002)
Actions by the Government of Canada, such as the Speech from the Throne in January 2001, the nomination of Minister Stéphane Dion to coordinate the Federal Government's policy on official languages and chair the team of Ministers directly involved in Official Languages Policy and Program and his desire to develop an action plan to support the application of the Official Languages Act are encouraging. The demonstration of the political will of the Government to fulfill its obligation to ensure the full support of the development of vibrant and healthy Official-language minority communities throughout Canada is absolutely essential. It is, thus, incumbent on the Government that there is understanding and acceptance of the needs and realities of each linguistic minority community by both the majority populations and by those within the Canadian Government whose job is to develop and implement policy in support of the Francophone and Anglophone minority communities. The Official Languages Act must ensure the means and mechanisms for coordinated action and mobilization of the necessary resources to empower official minority language communities. As such, the action plan put forward by Minister Dion must be aimed at enabling the English-speaking minority in Quebec to build its own capacity, using solid facts and broad-based knowledge to be able to work with all governments to maintain and develop strong, vibrant English-speaking communities throughout Quebec.

Strategic Intervention Plan : English Federal Correctional Services in Quebec - Quebec Community Groups Network (QCGN) (2021)

Stay Granted in First Court Challenge to Bill 96 - Quebec Community Groups Network (QCGN) (2022)

Statement by The Honourable Marlene Jennings, P.C. President of the Quebec Community Groups Network on the Adoption of BIll 96 - Quebec Community Groups Network (QCGN) (2022)

Special Consultations on Bill 40 : An Act to Amend Mainly the Education Act with Regard to School Organization and Governance - Quebec Community Groups Network (QCGN) (2019)
The Quebec Community Groups Network (“QCGN”) has not been invited to appear before the Committee in the course of its special consultations on Bill 40. Nonetheless, the QCGN submits this brief to the Committee. In addition to providing an excellent education to students, Quebec’s English public schools exist to preserve and promote the language and unique culture of English-speaking Quebec. The Government of Quebec must recognize and support the linguistic and cultural rights of Quebec’s English-speaking community. At the same time, the English-speaking community of Quebec recognizes the need for reforms. In 2015, the community conducted a wide-ranging consultation, and prepared recommendations to the Minister of Education and Higher Education on the matter. Bill 40 largely ignores those recommendations, particularly the recommendations for improving the electoral system. It does not reflect a model of education governance by and for the English- speaking community.
Keywords: Official Language Minority Community (OLMC)

Shutdown of Riverdale Destabilizing and Ill-advised : QCGN - Quebec Community Groups Network (QCGN) (2019)
Keywords: Official Language Minority Community (OLMC)

Senate Standing Committee on Official Languages (OLLO) : Study of C-13 An Act for the Substantive Equality of Canada's Official Languages - Quebec Community Groups Network (QCGN) (2023)
The QCGN has participated in every step of the modernization of the Official Languages Act, beginning with Bill S-209; an initiative of this Chamber led by the Honourable Maria Chaput. English-speaking Quebec worked closely and in good faith with our Francophone counterparts in the rest of Canada, Ministers of Canadian Heritage and Official Languages and this Committee during its historic study to modernize the Act, beginning in 2017.

Senate Probe of Language Law's Constitutional Effects Essential - QCGN - Quebec Community Groups Network (QCGN) (2023)

Selon un sondage, la plupart des Québécois, tant francophones qu’anglophones, souhaitent qu'Ottawa protège les droits des Québécois d'expression anglaise - Quebec Community Groups Network (QCGN) (2022)

Roadmap to Canada's Linguistic Duality 2008-2013 - Donnelly, Robert (2010)
Remarks to the Standing Committee on Official Language
Keywords: Official Language Minority Community (OLMC)

Response to Bill 40 : An Act to Amend Mainly the Education Act with Regard to School Organization - Quebec Federation of Home and School Associations (QFHSA) (2019)
On October 1, 2019, the CAQ Minister of Education and Higher Education Jean Francois Roberge tabled Bill 40, An Act to amend mainly the Education Act with regard to school organization and governance, fulfilling an election promise made by Premier Francois Legault to abolish school boards in Quebec. This lengthy and complex projet de loi affects more than 84 separate acts and regulations and we feel, proposes a governance model that is unnecessarily complex and unmanageable.

Resolution on the Definition of Quebec's English-speaking Community / Résolution concernant la définition de la communauté d'expression du Québec - Quebec Community Groups Network (QCGN) (2021)

Report of the Priority Setting Steering Committee Related to the 2018 Community Consultation - Quebec Community Groups Network (QCGN) (2018)
In March 2018, the Government of Canada renewed its official languages strategy, called the Action Plan for Official Languages 2018-2023: Investing in Our Future. Amongst other investments contained in the Action Plan, the Department of Canadian Heritage (PCH), was provided resources to increase the amount of funds available to the community sector through the Cooperation with the Community Sector – Development of Official Language Communities program, and, a development fund was established specifically for English-speaking Quebec.
Keywords: Official Language Minority Community (OLMC)

Recommandations du QCGN présentées dans le cadre de la Consultation prébudgétaire 2024-2025 - Quebec Community Groups Network (QCGN) (2024)
Keywords: Official Language Minority Community (OLMC)

Quietly Adopted Regulation Could Hurt Quality of Health Care for English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2022)

Quelle est la différence entre une langue commune et une langue officielle? - Quebec Community Groups Network (QCGN) (2023)

Quebecer's Views on Language Issues in the Aftermath of Bill 96 - Quebec Community Groups Network (QCGN); Association for Canadian Studies (ACS)

Quebec Should Help Our Institutions Deal with Financial Fallout of Government Policies - Quebec Community Groups Network (QCGN) (2024)

Quebec Must Drop Plans to Abandon the Riding of Westmount-Saint Louis - Quebec Community Groups Network (QCGN) (2016)

Quebec Community Groups Network Urges English-speaking Quebecers to Vote for Best Local Candidate - Quebec Community Groups Network (QCGN) (2021)

Quebec Community Groups Network: The Official Languages Act - Quebec Community Groups Network (QCGN) (2024)

Quebec Community Groups Network Preliminary Analysis of Bill C-13 : An Act for the Substantive Equality of Canada's Official Languages - Quebec Community Groups Network (QCGN) (2021)
This document presents an overview of Bill C-13. This is not a comprehensive analysis of the Bill. Rather, it is informed and directed at priority areas of the QCGN.

Quebec Community Groups Network Preliminary Analysis of Bill 96, An Act Respecting French, the Official and Common Langauge of Québec - Quebec Community Groups Network (QCGN) (2021)
Bill 96 is a wide-ranging and complex piece of legislation. It represents a significant overhaul of Quebec’s legal system. It amends the Charter of the French Language (“CFL”), 24 other provincial statutes, one regulation, and the Constitution Act, 1867.

Quebec Community Groups Network Brief to House of Commons Standing Committee on Official Languages : Full Implementation of the Official Languages Act in the Canadian Justice System - Quebec Community Groups Network (QCGN) (2017)
The Quebec Community Groups Network (QCGN) is pleased to submit the following brief to the House of Commons Standing Committee on Official Languages’ (LANG) study on the Full Implementation of the Official Languages Act in the Canadian Justice System. We understand the Committee’s objective is to examine how and to what extent the Official Languages Act is applied in areas of justice that fall under federal jurisdiction. The Committee should know that English-speaking Quebec does not yet possess the level of capacity in this sector represented by organizations like the Fédération des associations de juristes d'expression française de common law, the Centre canadien de français juridique, or the Réseau national de formation en justice. We do not have researched and coherent policy proposals, nor even a developed Quebec-wide network of English-speaking jurists. We are hopeful however that this capacity will develop, and the QCGN continues to actively support the newly formed Association of English-speaking Jurists of Quebec (AESJQ), who have submitted their own brief towards this study.
Keywords: Official Language Minority Community (OLMC)

Quebec Community Groups Network Brief to Committee on Culture and Education : Special Consultations on Bill 40: An Act to amend mainly the Education Act with regard to school organization and governance - Quebec Community Groups Network (QCGN) (2019)
The Quebec Community Groups Network (“QCGN”) has not been invited to appear before the Committee in the course of its special consultations on Bill 40. Nonetheless, the QCGN submits this brief to the Committee. In addition to providing an excellent education to students, Quebec’s English public schools exist to preserve and promote the language and unique culture of English-speaking Quebec. Schools are key and central institutions of the English-speaking community of Quebec. The Government of Quebec must recognize and support the linguistic and cultural rights of Quebec’s English-speaking community. Management and control of our educational institutions cannot be unilaterally restricted. At the same time, the English-speaking community of Quebec recognizes the need for reforms to the governance of its educational institutions.
Keywords: Official Language Minority Community (OLMC)

Quebec Community Groups Network analyse préliminaire du projet de loi C-13 : Loi visant l’égalité réelle entre les langues officielles du Canada - Quebec Community Groups Network (QCGN) (2021)
Rappelons que le présent document offre un aperçu du projet de loi C-13. Il ne s'agit pas d'une analyse exhaustive du projet de loi. Elle soutient et s’oriente plutôt vers les domaines prioritaires du QCGN.

Quebec Community Groups Network Access to Justice in English in Quebec - Working Together to Ensure Access to Justice in English in Quebec - Quebec Community Groups Network (QCGN)

Quebec Budget Must Address Underfunding of Our Community Groups : QCGN - Quebec Community Groups Network (QCGN) (2023)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2012)

QCGN Wraps Up Annual Meeting Resolved to be a Strong Voice for English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2023)

QCGN wraps up 24th Annual General Meeting Prepared to Face Government Threats - Quebec Community Groups Network (QCGN) (2019)
Keywords: Official Language Minority Community (OLMC)

QCGN Welcomes Senate Report that Calls for Equality of French and English Language Rights - Quebec Community Groups Network (QCGN) (2022)

QCGN Welcomes Quebec Budget Support for English-speaking Community - Quebec Community Groups Network (QCGN) (2023)

QCGN Welcomes Promises of New Investments in Official Languages - Quebec Community Groups Network (QCGN) (2018)

QCGN Welcomes Nomination of Kathleen Weil as Minister Responsible for Relations with English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2017)

QCGN Welcomes New Federal Investments in English-speaking Quebec - Quebec Community Groups Network (QCGN) (2018)
Keywords: Official Language Minority Community (OLMC)

QCGN Welcomes New Budget Measures for English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2018)

QCGN Welcomes Creation of New Secretariat in Premier's Office - Quebec Community Groups Network (QCGN) (2017)

QCGN Welcomes Canadian Heritage Minister and Bids Adieu to President and Commissioner - Quebec Community Groups Network (QCGN) (2016)

QCGN Wants New Parliament to Ensure Respect for English and French as the Official Languages of Canada - Quebec Community Groups Network (QCGN) (2019)
Keywords: Official Language Minority Community (OLMC)

QCGN Urges Quebec Government to Backtrack on Bill 96 - Quebec Community Groups Network (QCGN) (2021)

QCGN Urges All Participants in Debate Over Bill 96 to Act with Civility and Respect - Quebec Community Groups Network (QCGN) (2021)

QCGN Supports Intent of Chaput Bill (Bill S-205) - Quebec Community Groups Network (QCGN) (2014)

QCGN Supports Commissioner's Call for Symmetry in the Official Languages Act - Quebec Community Groups Network (QCGN) (2021)

QCGN Supports Commissioner's Call for a More Effective Official Languages Act - Quebec Community Groups Network (QCGN) (2019)
Keywords: Official Language Minority Community (OLMC)

QCGN Statement on The Expert Panel on Language of Work and Service in Federally Regulated Private Businesses - Quebec Community Groups Network (QCGN) (2020)

QCGN Statement on Superior Court Ruling on Quebec’s Secularism Law : A Good Day for Minority Education Right - Quebec Community Groups Network (QCGN) (2021)

QCGN Statement on National Assembly Hearings on Bill 96 : QCGN Calls for Broader Participation in Bill 96 Hearings - Quebec Community Groups Network (QCGN) (2021)

QCGN Statement on National Assembly Hearings on Bill 96 : QCGN Calls for Broader Participation in Bill 96 Hearings - Quebec Community Groups Network (QCGN) (2021)

QCGN Statement on Government of Canada’s Proposed Changes to the Official Languages Act - Quebec Community Groups Network (QCGN) (2021)

QCGN Statement on Bloc Québécois report on federal funding for Quebec’s English-speaking minority - Quebec Community Groups Network (QCGN) (2023)

QCGN Statement on Bill 15 and Closure - Quebec Community Groups Network (QCGN) (2023)

QCGN Shares Concerns Over Selection Process for Commissioner of Official Languages - Quebec Community Groups Network (QCGN) (2017)
Keywords: Official Language Minority Community (OLMC)

QCGN Set To Champion English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2018)
Keywords: Official Language Minority Community (OLMC)

QCGN Recommendations to the 2024–2025 Pre-Budget Consultation - Quebec Community Groups Network (QCGN) (2024)
Keywords: Official Language Minority Community (OLMC)

QCGN Reacts to An Act to Amend the Official Languages Act, to Enact the Use of French in Federally Regulated Private Business Act - Quebec Community Groups Network (QCGN) (2022)

QCGN Proposes Major Amendments to Federal Bill Modernizing the Official Languages Act - Quebec Community Groups Network (QCGN) (2022)

QCGN Praises Commissioner Fraser for a Decade of Support to Quebec's English-speaking Community - Quebec Community Groups Network (QCGN) (2016)

QCGN Pleased with Renewed Support for English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2019)
Keywords: Official Language Minority Community (OLMC)

QCGN Organizes Parallel Bill 96 Consultation - Quebec Community Groups Network (QCGN) (2021)

QCGN Opening Remarks to Committee on Culture and Education : General consultation and public hearings on Bill 14: An Act to Amend the Charter of the French Language, the Charter of Human Rights and Freedoms and Other Legislative Provisions - Quebec Community Groups Network (QCGN) (2013)

QCGN Members Strongly Endorse Battle Against Laws and Policies Eroding the Rights of English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2022)

QCGN Looks Forward to Working Together with Premier François Legault and His New Cabinet - Quebec Community Groups Network (QCGN) (2018)

QCGN Looks Forward to Champion for All Official Language Minority Communities - Quebec Community Groups Network (QCGN) (2017)
Keywords: Official Language Minority Community (OLMC)

QCGN Implores Senate Committee to Withdraw Mentions of Quebec's Charter of the French Language from Official Languages Act Overhaul - Quebec Community Groups Network (QCGN) (2023)
Keywords: Official Language Minority Community (OLMC)

QCGN Hosts Virtual Town Hall with Éric Duhaime - Quebec Community Groups Network (QCGN) (2022)

QCGN Hosts Virtual Town Hall with Dominique Anglade - Quebec Community Groups Network (QCGN) (2022)

QCGN Hosts Virtual Town Hall with Colin Standish - Quebec Community Groups Network (QCGN) (2022)

QCGN Hosts Virtual Town Hall with Balarama Holness - Quebec Community Groups Network (QCGN) (2022)

QCGN Has New Interim President and Renewed Resolve to Battle Bill 96 and Other Legislation Detrimental to English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2022)

QCGN Expresses Serious Misgivings About Vague Government Consultation Plan - Quebec Community Groups Network (QCGN) (2019)

QCGN Eager to Work on Modernization of Official Languages Act - Quebec Community Groups Network (QCGN) (2021)

QCGN Eager to Contribute to Hearings on Modernization of the Official Languages Act - Quebec Community Groups Network (QCGN) (2019)
Keywords: Official Language Minority Community (OLMC)

QCGN Discusses Concerns of English-speaking Community with Premier Couillard - Quebec Community Groups Network (QCGN) (2016)

QCGN Demands Apology from Prime Minister Trudeau - Quebec Community Groups Network (QCGN) (2016)
Keywords: Official Language Minority Community (OLMC)

QCGN deeply disappointed Canada's Official Language Act will contain references to Quebec's Charter of the French Language - Quebec Community Groups Network (QCGN) (2023)

QCGN Congratulates Eric Girard, New Minister Responsible for Relations with English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2022)

QCGN/Community Pleased with Funding from Secretariat - Quebec Community Groups Network (QCGN) (2018)

QCGN Cautiously Optimistic About Ottawa's Plan to Overhaul the Official Languages Act - Quebec Community Groups Network (QCGN) (2021)

QCGN Calls on Premier Legault to Support English-speaking Community - Quebec Community Groups Network (QCGN) (2019)

QCGN Calls on Federal Parties and Candidates to Support the Language Rights of English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2021)

QCGN Calls for More Study and Debate on Quebec's Proposal : Poll Show Unilateral Amendment to Constitution of Canada Worries Most Canadians and Some Quebecers - Quebec Community Groups Network (QCGN) (2021)

QCGN Board Responds to Public Withdrawal of Board Members - Quebec Community Groups Network (QCGN) (2019)

QCGN Board of Directors : Resolution Regarding Bill 14, An Act to Amend the Charter of the French Language, the Charter of Human Rights and Freedoms and other Legislative Provisions, Tabled in the National Assembly of Quebec on December 5, 2012 - Quebec Community Groups Network (QCGN) (2013)

QCGN Begs to Differ on Premier's Interpretation of English Signage in Hospitals - Quebec Community Groups Network (QCGN) (2019)

QCGN Asks New Parliament to Deliver Improved Official Languages Act - Quebec Community Groups Network (QCGN) (2019)
Keywords: Official Language Minority Community (OLMC)

QCGN Asks Government to Exclude English School Boards from Education Reform Plan - Quebec Community Groups Network (QCGN) (2019)

QCGN Appearance before the House of Commons Standing Committee on Official Languages - Quebec Community Groups Network (QCGN) (2016)

QCGN Analysis of Quebec's Five Orientations to Modernize Canada's OfficialLanguages Act - Quebec Community Groups Network (QCGN) (2021)
Quebec’s proposal belies a fundamental misunderstanding of the history, purpose, and application of the OLA. It takes direct aim at the division of powers contained in the Constitution Act, 1867, seeking to extend Quebec’s legislative jurisdiction. The Government of Quebec is demanding exclusive authority to act in matters of language, “on its territory”. This poses an existential threat to the official language rights of all Canadians, French and English.

QCGN Advocates a More Community-driven Process for Provincial Funding - Quebec Community Groups Network (QCGN) (2018)

Provincial Budget Prioritizes Health, Education, and Economic Recovery : QCGN Pleased with New Spending to Support English-speaking Minority - Quebec Community Groups Network (QCGN) (2021)

Proposed Bill 101 Overhaul Disgregards Fundamental Human Rights and Freedoms - Quebec Community Groups Network (QCGN) (2021)

Projet de loi 96 – débat de la commission à l’assemblée nationale concernant la clause portant sur la minorité « historique anglophone » - Quebec Community Groups Network (QCGN) (2022)

Projet Accès à la justice en anglais : Services de soins aux personnes âgées en anglais au Québec : Sommaire du rapport final et recommandations au Ministère de la Santé et des Services sociaux - Quebec Community Groups Network (QCGN) (2023)

Projet Accès à la justice en anglais: Accès aux tribunaux du Québec en anglais : Sommaire et recommandations - Quebec Community Groups Network (QCGN) (2023)
Le projet Accès à la justice en anglais du QCGN repère et recherche les domaines où la communauté d’expression anglaise éprouve des difficultés à faire valoir ses droits en mettant l'accent sur l'accès de la communauté aux services publics. Il utilise l'information comme ressource stratégique pour comprendre et améliorer l'accès à la justice en anglais au Québec.

Projet Accès à la justice en anglais : Accès aux sites Web du gouvernement du Québec en anglais : Rapport exécutif et recommandations - Quebec Community Groups Network (QCGN) (2023)
Le projet Accès à la justice en anglais du QCGN (« le Projet ») repère et recherche les domaines où la communauté d’expression anglaise éprouve des difficultés à accéder à ses droits en mettant l'accent sur l'accès des communautés aux services publics. Il utilise l'information comme une ressource stratégique pour comprendre et améliorer l'accès à la justice en anglais au Québec.

Priority Setting Steering Committee Phase II Recommendations to the Department of Canadian Heritage - Quebec Community Groups Network (QCGN) (2018)
In March 2018, the Government of Canada renewed its official languages strategy, called the Action Plan for Official Languages 2018-2023: Investing in Our Future. Amongst other investments in the Action Plan, the Department of Canadian Heritage (PCH) announced increased funding for English-language minority community organizations in Quebec. This increase is to be delivered through the Official Languages Funding Programs in two sub-components: 1) Cooperation with the Community Sector 2) a new Development Fund established specifically for English-speaking Quebec. In May 2018, the Minister of Canadian Heritage requested that representative organizations provide input on behalf of Canada’s official language minority communities, on principles and priorities for action and to guide decisions on the allocation of new financial resources for programs and projects undertaken by and for these communities through her Department. The Quebec Community Groups Network (QCGN) – English-speaking Quebec’s official interlocutor with PCH – accepted this task, and at a special meeting of its Board of Directors on June 16, tasked the Priority Setting Steering Committee (PSSC) with undertaking the work.
Keywords: Official Language Minority Community (OLMC)

Presentation to the Standing Committee on Official Languages on Immigration as a Development Tool in Official Language Minority Communities - Quebec Community Groups Network (QCGN) (2010)

Presentation to the Committee on Culture and Education on Bill 86 - Duszara, Walter; Chambers, Geoffrey; Maldoff, Eric; Martin-Laforge, Sylvia (2017)

Premier's Re-election Provides Opportunity for a Fresh Start : QCGN Calls for Appointment of a Dedicated Minister Responsible for Relations with English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2022)

Premier Legault Attempts to Muzzle English-speaking Community - Quebec Community Groups Network (QCGN) (2020)
Keywords: Official Language Minority Community (OLMC)

Preliminary Analysis of Bill C-13, An Act for the Substantive Equality of Canada's Official Languages - Quebec Community Groups Network (QCGN) (2021)
Like Bill C-32, the Bill retains the same overall purposes and structure of the OLA. As with Bill C-32, the Bill sets out several new Preamble clauses, additions to the OLA’s purpose clause, and new interpretive clauses. These are all largely the same as Bill C-32, although the Bill adds a few additional clauses. In the discussion below, there is no change from C-32 except where otherwise indicated. The Bill adds the following policy priorities to the OLA: First, the protection and promotion of the French language; second, the addition of new interpretive clauses; third, the continued recognition of English and French linguistic minority communities (OLMC’s); third, the recognition of provincial language regimes including the Charter of the French Language. Finally, the Bill adds additional mention of Indigenous languages and a mention that the OLA applies in emergencies
Keywords: Official Language Minority Community (OLMC)

Petition demands rethink of Bill 15’s radical revamp of Health Care Network - Quebec Community Groups Network (QCGN) (2023)

Participation of English-speaking Canadians in the Federal Civil Service in Quebec (outside of the National Capital Region) - Quebec Community Groups Network (QCGN) (2018)

Overview of Proposed Amendments to the Lobbying Act (Québec) : Bill 56 Lobbying Transparency Act - Quebec Community Groups Network (QCGN) (2015)

Opposition Grows to Restrictive Definition of English-speaking Community - Quebec Community Groups Network (QCGN) (2021)

Opposition Grows to Premier’s Pigeonholing of ‘Historic Anglos’ - Quebec Community Groups Network (QCGN) (2021)

Opposition croissante à l’expression « anglophones historiques » du premier ministre - Quebec Community Groups Network (QCGN) (2021)

Opening Remarks of Marlene Jennings, President of QCGN, to QCGN Hearings on Bill 96 - Jennings, Marlene (2021)

Opening Remarks by QCGN President, the Honourable Marlene Jennings, P.C., LLB to the Committee on Culture and Education : Special Consultations and Public Hearings on Bill 96, an Act Respecting French, the Official and Common Language of Quebec - Jennings, Marlene (2021)

Open Letter to Minister Simon Jolin-Barrette from Marlene Jennings - Quebec Community Groups Network (QCGN) (2021)

On Amending the Constitution and Recognizing the Quebec Nation - Quebec Community Groups Network (QCGN); Association for Canadian Studies (ACS) (2021)

No Time to Waste before Government Imposes Massive Centralization of Health and Social Services – and Adds a New Threat to English Access - Quebec Community Groups Network (QCGN) (2023)

New Official Languages Act Must Safeguard the Minority Language Rights of English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2022)

Network News - Quebec Community Groups Network (QCGN) (2017)

Network News - Quebec Community Groups Network (QCGN) (2017)

Network News - Quebec Community Groups Network (QCGN) (2018)

Network News - Quebec Community Groups Network (QCGN) (2018)

Network News - Quebec Community Groups Network (QCGN) (2018)

Network News - Quebec Community Groups Network (QCGN) (2019)

Network News - Quebec Community Groups Network (QCGN) (2019)

Network News - Quebec Community Groups Network (QCGN) (2019)

Network News - Quebec Community Groups Network (QCGN) (2020)

Network News - Quebec Community Groups Network (QCGN) (2021)

Network News - Quebec Community Groups Network (QCGN) (2021)

Network News - Quebec Community Groups Network (QCGN) (2021)

Network News - Quebec Community Groups Network (QCGN) (2021)

Network News - Quebec Community Groups Network (QCGN) (2021)

Network News - Quebec Community Groups Network (QCGN) (2022)

Network News - Quebec Community Groups Network (QCGN) (2022)

Network News - Quebec Community Groups Network (QCGN) (2022)

Network News - Quebec Community Groups Network (QCGN) (2022)

Network News - Quebec Community Groups Network (QCGN) (2022)

Network News - Quebec Community Groups Network (QCGN) (2022)

Network News - Quebec Community Groups Network (QCGN) (2022)

Network News - Quebec Community Groups Network (QCGN) (2023)

Network News - Quebec Community Groups Network (QCGN) (2023)

Network News - Quebec Community Groups Network (QCGN) (2023)

Network News - Quebec Community Groups Network (QCGN) (2023)

Network News - Quebec Community Groups Network (QCGN) (2024)

National Assembly Walks Back "3 Content Courses in French" Rule for English CEGEPs - Quebec Community Groups Network (QCGN) (2022)

National Assembly Adopts Bill 96 - Quebec Community Groups Network (QCGN) (2022)

Mot d’ouverture de Marlene Jennings, présidente du QCGN, lors des audiences publiques du QCGN sur le projet de loi no 96 - Jennings, Marlene (2021)

Most Quebecers, English and French, Want Ottawa to Protect Rights of English-speaking Quebecers : Poll - Quebec Community Groups Network (QCGN) (2022)

More English-speaking Quebecers Reject Divisive ‘Historic Anglo’ Approach - Quebec Community Groups Network (QCGN) (2022)

Modernizing the Official Languages Act : How the Federal Government Got it Wrong with C-13 - Quebec Community Groups Network (QCGN) (2022)

Mémoire présenté dans le cadre de la consultation prébudgétaire 2024-2025 - Quebec Community Groups Network (QCGN) (2024)

Mémoire présenté au Comité permanent du patrimoine canadien : Cultiver la vitalité des médias dans les communautés minoritaires d’expression anglaise du Québec - Quebec Community Groups Network (QCGN) (2016)
Les Québécois d’expression anglaise ont toujours exprimé leur besoin impérieux et prioritaire d’avoir accès à de l’information dans leur propre langue (sondage CROP réalisé pour le Réseau communautaire de santé et de services sociaux [RCSSS], diverses années). Cette affirmation peut sembler quelque peu contradictoire dans un monde inondé d’informations de langue anglaise par CNN, le magazine Time et la profusion de films hollywoodiens. Une nuance importante est que les Québécois d’expression anglaise ont besoin d’informations dans leur langue concernant leurs propres communautés locales et régionales. Il s’agit là de quelque chose qui est de plus en plus difficile à obtenir de façon régulière dans le contexte de la francisation de la vie quotidienne au Québec et de la disparition des médias communautaires traditionnels.

Mémoire présenté au Comité permanent des langues officielles de la Chambre des communes : Projet de loi C-13, Loi visant l’égalité réelle entre les langues officielles du Canada - Quebec Community Groups Network (QCGN) (2022)
La Loi sur les langues officielles (LLO) représente une bouée de sauvetage pour le Québec d’expression anglaise et, compte tenu du projet de loi 96 du Québec, la communauté anglophone en a besoin plus que jamais. Mais avec le projet de loi C-13, cette bouée de sauvetage s'effiloche. Fondé en 1995, le Quebec Community Groups Network (QCGN) est un organisme à but non lucratif qui relie les organismes communautaires de langue anglaise partout au Québec. Le QCGN — tout comme les communautés qu'il sert — est fier de soutenir la protection et la promotion de la langue française au Canada. Le QCGN milite en faveur de la dualité linguistique dans chaque province et chaque territoire. La minorité d’expression anglaise du Québec est une communauté diversifiée, bilingue et résiliente, qui est confrontée à de sérieux défis économiques ainsi qu’à des mythes et à des stéréotypes persistants. Bien que sa langue elle-même ne soit pas menacée, le défi de la communauté d’expression anglaise consiste à préserver sa vitalité et sa survie dans toutes les régions du Québec.
Keywords: Official Language Minority Community (OLMC)

Mémoire présenté à la Consultation prébudgétaire mené par Eric Girard, ministre des Finances du Québec - Quebec Community Groups Network (QCGN) (2023)
Les section A à C de ce mémoire traitent des besoins de financement des organismes du secteur communautaire du Québec, et plus particulièrement des besoins des organismes qui offrent des services et des programmes aux Québécois d'expression anglaise. Le Quebec Community Groups Network (QCGN) a depuis longtemps le mandat de recueillir, de colliger et d'articuler les besoins de la communauté d'expression anglaise du Québec, et le travail que nous avons effectué dans ce dossier au cours des dernières années a considérablement éclairé ces sections de notre mémoire.

Mémoire présenté à la Commission de la culture et de l’éducation de l’Assemblée nationale en regard à la consultation générale et auditions publiques sur le projet de loi n°14, Loi modifiant la Charte de la langue française, la Charte des droits et libertés de la personne et d’autres dispositions législatives - Quebec Community Groups Network (QCGN) (2013)
Ce mémoire a été rédigé par le Quebec Community Groups Network (QCGN), un organisme à but non lucratif dont la mission est de cerner, de clarifier et de traiter les enjeux stratégiques qui affectent le développement durable et la vitalité du Québec d’expression anglaise. Le QCGN et ses 41 organismes membres travaillent ensemble et avec les intervenants communautaires, les leaders, les gouvernements et les institutions, pour faire valoir les intérêts de notre communauté en situation minoritaire.

Mémoire du Quebec Community Groups Network déposé à la Commission de la santé et des services sociaux de l’Assemblée nationale du Québec : Le projet de loi n° 10, loi visant à modifier l’organisation et la gouvernance du réseau de la santé et des services sociaux, notamment par l’abolition des agences régionales - Quebec Community Groups Network (QCGN) (2014)

Mémoire du Quebec Community Groups Network CGN à la Commission de la culture et de l’éducation : Consultations particulières sur le projet de loi 40 : Loi modifiant principalement la Loi sur l’instruction publique relativement à l’organisation et à la gouvernance scolaires - Quebec Community Groups Network (QCGN) (2019)
Le Quebec Community Groups Network (QCGN) n’a pas été invité à comparaître devant la Commission dans le cadre de ses consultations particulières sur le projet de loi 40. Néanmoins, le QCGN soumet le présent mémoire à la Commission. En plus d’offrir un enseignement d’excellente qualité aux élèves, les écoles publiques anglophones ont pour mission de préserver et de promouvoir la langue et la culture distinctes du Québec d’expression anglaise. Les écoles sont des institutions essentielles et centrales de la communauté d’expression anglaise du Québec. Le gouvernement du Québec doit ainsi reconnaître et appuyer les droits linguistiques et culturels de cette communauté. La gestion et le contrôle de nos établissements d’enseignement ne peuvent être limités unilatéralement.
Keywords: Official Language Minority Community (OLMC)

Mémoire à la Commission de la culture et de l’éducation : Le Québec et les droits à l’instruction dans la langue de la minorité, et les communautés d’expression anglaise en situation minoritaire au Canada : Un nouveau partenariat - Quebec Community Groups Network (QCGN) (2016)
Voter aux élections est un droit intrinsèque pour tous les Québécois. Mais le gouvernement va à l’encontre de sa tradition démocratique en révoquant capricieusement ce droit sans aucune raison impérieuse ou importante. Le système d’écoles publiques anglophones du Québec est une institution qui joue un rôle clé au sein de la communauté d’expression anglaise de la province — une communauté linguistique en situation minoritaire. La gestion et le contrôle de ces institutions sont une question de gouvernance qui touche les droits à l’instruction dans la langue de la minorité, ces droits étant enchâssés dans la Charte canadienne des droits et libertés et dans la tradition démocratique du Québec, ainsi qu’exprimés dans les droits politiques garantis par la Charte des droits et libertés de la personne du Québec. Le gouvernement du Québec a le devoir de reconnaître sa communauté linguistique minoritaire et de travailler en partenariat avec elle afin de garantir la gestion et le contrôle efficaces du système d’écoles publiques anglophones.
Keywords: Official Language Minority Community (OLMC)

Mémoire à la Commission de la culture et de l’éducation : Consultations particulières et audiences publiques sur le projet de loi no 105 : Loi modifiant la Loi sur l’instruction publique - Quebec Community Groups Network (QCGN) (2016)
Le Quebec Community Groups Network (QCGN) est un organisme qui représente quarante-huit (48) groupes communautaires d’expression anglaise, répartis dans l’ensemble du Québec. Le QCGN reconnaît que le système scolaire public anglais du Québec est une institution qui joue un rôle de premier plan dans la communauté d’expression anglaise de la province – une communauté linguistique minoritaire. La gestion et le contrôle de ses institutions sont une question de gouvernance sujette aux droits à l’instruction dans la langue de la minorité. Enchâssés dans la Charte canadienne des droits et libertés et dans la tradition démocratique québécoise, ces droits sont également énoncés et garantis par la Charte des droits et libertés de la personne du Québec.
Keywords: Official Language Minority Community (OLMC)

Make the Case Report : Access to Senior Care in English in Quebec : A research analysis of English language rights in Quebec health care and access to the SAPA program for English-speaking seniors in Quebec - Quebec Community Groups Network (QCGN) (2023)
This report discusses and details one of the AJEQ Project’s candidate issues of research: access to senior health care services in English in Quebec’s SAPA program (Soutien à l’autonomie des personnes âgées). The issue was selected on the basis of prior research conducted by the AJEQ Project, including a population survey of 1,601 English-speaking Quebecers conducted by Quorus Consulting Group in September 2021, which revealed that hospitals and CLSC care were among the most widely accessed provincial government services by English-speaking Quebecers, and that more than one in three English-speaking Quebecers who had accessed these services in the past two years found it difficult to do so in English. The issue of senior care was under close scrutiny at the time the issue was selected, in the wake of the COVID-19 pandemic and the subsequent coroner’s inquiry into pandemic-related deaths at seniors’ residences across Quebec.

Long Awaited Regulation Creating Provincial Access to Committee a First Step in the Right Direction - Quebec Community Groups Network (QCGN) (2018)

Lettre ouverte de Marlene Jennings à l’intention du ministre Simon Jolin Barrette - Quebec Community Groups Network (QCGN) (2021)

[Letter to Premier Couillard re: English Schools / Lettre au premier ministre Couillard concernant les écoles anglaises] - Quebec Community Groups Network (QCGN) (2015)

[Letter to Maxime Perrault from James Shea, QCGN President, re: Bil 62] - Shea, James (2016)

[Letter to House Leaders from Geoffrey Chambers, QCGN President] - Chambers, Geoffrey (2020)

[Letter re: Bill 10 - Letters of Support of QCGN] - Committee for Anglophone Social Action (CASA); Coasters Association; Community Health and Social Services Network (CHSSN); Jeffery Hale - Saint Brigid's (JHSB); Neighbours Regional Association of Rouyn-Noranda; Quebec Community Groups Network (QCGN); Quebec Federation of Home and School Associations (QFHSA) (2014)

Letter of Support for QCGN - Zucchi, John (2014)

Les droits linguistiques établis dans la loi sur la santé publique ne seront pas liés à la définition « d’anglophone historique » - Quebec Community Groups Network (QCGN) (2022)

Les droits collectifs et la vitalité en déclin des communautés québécoises d’expression anglaise : Mémoire présenté à la Commission de la culture et de l’éducation dans le cadre de la consultation générale et des audiences publiques sur le projet de loi numéro 103, loi modifiant la Charte de la langue française et d’autres dispositions législatives - Quebec Community Groups Network (QCGN) (2010)
Our brief deals with the declining vitality of the English-speaking communities of Quebec (ESCQ) and the relative strength of the Francophone majority. The QCGN‟s goal is to demonstrate that our minority communities are not a threat to the majority, but a constituency that strengthens Quebec society. We expose the detrimental effect that Quebec's habit of emphasising an exclusionary notion of its society has on its minority population. Finally, we seek to attain official recognition of the historic and ongoing contributions our minority makes to Quebec society and achieve legal protection of minority rights and freedoms.
Keywords: Official Language Minority Community (OLMC)

Legislative Update, Bill C-13 An Act to Amend the Official Languages Act, to Enact the Use of French in Federally Regulated Private Businesses Act and to Make Related Amendments to Other Acts - Quebec Community Groups Network (QCGN) (2022)

Le Québec devrait aider nos institutions à faire face aux retombées financières des politiques gouvernementales - Quebec Community Groups Network (QCGN) (2024)

Le QCGN salue le soutien accordé à la communauté d'expression anglaise dans le budget du Québec - Quebec Community Groups Network (QCGN) (2023)

Le QCGN réagit à la Loi modifiant la Loi sur les langues officielles et édictant la Loi sur l'utilisation du français dans les entreprises privées sous réglementation fédérale - Quebec Community Groups Network (QCGN) (2022)

Le QCGN propose des modifications majeures au projet de loi fédéral visant à moderniser la Loi sur les langues officielles - Quebec Community Groups Network (QCGN) (2022)

Le QCGN prie instamment le Comité sénatorial de retirer les mentions de la Charte de la langue française du Québec de la refonte de la Loi sur les langues officielles - Quebec Community Groups Network (QCGN) (2023)
Keywords: Official Language Minority Community (OLMC)

Le QCGN organise une consultation parallèle sur le projet de loi 96 - Quebec Community Groups Network (QCGN) (2021)

Le QCGN juge primordial que le Sénat examine les effets constitutionnels du projet de loi sur les langues officielles - Quebec Community Groups Network (QCGN) (2023)

Le QCGN félicite Éric Girard, nouveau ministre responsable des Relations avec les Québécois d’expression anglaise - Quebec Community Groups Network (QCGN) (2022)

Le QCGN exprime sa profonde déception quant à l’insertion des références à la Charte de la langue française du Québec dans la Loi sur les langues officielles du Canada - Quebec Community Groups Network (QCGN) (2023)

Le QCGN exhorte tous les participants au débat sur le projet de loi no 96 à faire preuve de courtoisie et de respect - Quebec Community Groups Network (QCGN) (2021)

Le QCGN exhorte le gouvernement du Québec à faire marche arrière au sujet du projet de loi 96 - Quebec Community Groups Network (QCGN) (2021)

Le QCGN demande la nomination d’un ministre responsable des Relations avec les Québécois d’expression anglaise - Quebec Community Groups Network (QCGN) (2022)

Le QCGN demande aux partis et aux candidats fédéraux de défendre les droits linguistiques des Québécois d’expression anglaise - Quebec Community Groups Network (QCGN) (2021)

Le QCGN clôture son assemblée annuelle, résolu à défendre haut et fort les droits des Québécois d'expression anglaise - Quebec Community Groups Network (QCGN) (2023)

Le QCGN accueille favorablement le rapport du Sénat qui préconise l'égalité des droits linguistiques des francophones et des anglophones - Quebec Community Groups Network (QCGN) (2022)

Le QCGN a une nouvelle présidente intérimaire et une détermination renouvelée de lutter contre la loi 96 et autres mesures législatives néfastes pour les Québécois d’expression anglaise - Quebec Community Groups Network (QCGN) (2022)

Le projet de loi no 96 et la communauté sourde : les conséquences imprévues de la législation - Quebec Community Groups Network (QCGN) (2021)

Le projet de loi no 96 est mal conçu et doit être retiré - Quebec Community Groups Network (QCGN) (2021)

Le projet de loi C-13 affaiblit la bouée de sauvetage fédérale des Québécois d’expression anglaise au moment où ils en ont le plus besoin - Quebec Community Groups Network (QCGN) (2021)

Le projet de loi 40 a violé les droits à l’instruction de la minorité d’expression anglaise tranche la Cour supérieure - Quebec Community Groups Network (QCGN) (2023)

Le Plan d'action pour les langues officielles ouvre des opportunités pour la communauté d’expression anglaise du Québec - Quebec Community Groups Network (QCGN) (2023)
Keywords: Official Language Minority Community (OLMC)

Le ministre de la Langue française propose six nouveaux amendements au projet de loi 96 concernant les transactions commerciales en ligne, les obligations du commissaire et la force exécutoire des contrats - Quebec Community Groups Network (QCGN) (2022)

Le Canada, le Québec et les accords intergouvernementaux à l'appui des Québécois d'expression anglaise - Quebec Community Groups Network (QCGN) (2023)

Le budget fédéral prévoit de nouveaux fonds pour les minorités de langue officielle - Quebec Community Groups Network (QCGN) (2023)

Le budget du Québec doit s'attaquer au sous-financement de nos groupes communautaires : QCGN - Quebec Community Groups Network (QCGN) (2023)

Language Rights Under Health Act Will Not be Tied to 'Historic Anglophone' Definition - Quebec Community Groups Network (QCGN) (2022)

Language Minorities Need Separate Rights Support Program - Quebec Community Groups Network (QCGN) (2016)

Lancement d’une pétition pour la révision de la réforme radicale du réseau de la santé prévue par le projet de loi 15 - Quebec Community Groups Network (QCGN) (2023)

La politique scandaleuse de la Coalition Avenir Québec en matière de frais de scolarité nuit à tous les Québécois - Quebec Community Groups Network (QCGN) (2023)

La pétition concernant le projet de loi 15 recueille 6400 signatures en 16 jours - Quebec Community Groups Network (QCGN) (2023)

La commission poursuit ses discussions concernant les restrictions relatives aux admissions dans les CÉGEPS - Quebec Community Groups Network (QCGN) (2022)

La Commission poursuit ses débats sur l'avenir des CÉGEPS de langue anglais - Quebec Community Groups Network (QCGN) (2022)

La Commission modifie de manière substantielle les lois québécoises relatives aux droits de la personne - Quebec Community Groups Network (QCGN) (2022)

La Commission mène à terme l'étude du projet de loi 96 : la CAQ consacre la primauté de la langue française de la "Nation Québécoise" sur les chartes Canadienne et Québécoise des droits de la personne - Quebec Community Groups Network (QCGN) (2022)

La commission examine les règles relatives à l’affichage des postes bilingues - Quebec Community Groups Network (QCGN) (2022)

La commission examine les règles linguistiques régissant le milieu des affaires et l’éducation publique - Quebec Community Groups Network (QCGN) (2022)

La commission examine les effets des directives des agences sur les immigrants du Québec - Quebec Community Groups Network (QCGN) (2022)

La commission examine l’obligation des professionnels de fournir leur documentation en français - Quebec Community Groups Network (QCGN) (2022)

La commission entreprend l’examen des restrictions linguistiques relatives aux admissions au CEGEP - Quebec Community Groups Network (QCGN) (2022)

La Commission discute de la qualité du français enseigné aux nouveaux arrivants et aux anglophones - Quebec Community Groups Network (QCGN) (2022)

La Commission discute de la création de Francisation Québec et d'un ministère de la langue française - Quebec Community Groups Network (QCGN) (2022)

La Commission discute de l'usage du français au sein des enterprises - Quebec Community Groups Network (QCGN) (2022)

La commission continue de prévoir des exceptions à l’usage exemplaire de la langue française - Quebec Community Groups Network (QCGN) (2022)

La Commission clôt le débat sur les cégeps et se penche sur les universités - Quebec Community Groups Network (QCGN) (2022)

La Commission ajoute de nouvelles mesures punitives au projet de loi 96 - Quebec Community Groups Network (QCGN) (2022)

La Commission adopte une série de changements surprenants en matière de bilinguisme concernant les nominations à la magistrature du Québec - Quebec Community Groups Network (QCGN) (2022)

La Commission adopte les modifications proposées au Code civil du Québec - Quebec Community Groups Network (QCGN) (2022)

L’impact réel du projet de loi 96 sur la communauté d’expression anglaise est on ne peut plus clair - Quebec Community Groups Network (QCGN) (2021)

L'Assemblée nationale revient sur la règle des "Trois cours du programmes enseignés en français" dans les Cégeps anglophones - Quebec Community Groups Network (QCGN) (2022)

L'Assemblée nationale adopte le projet de loi 96 - Quebec Community Groups Network (QCGN) (2022)

Immigration : A perspective from Quebec's English-speaking communities : Prepared for the special National Assembly Committee on Immigration - Quebec Community Groups Network (QCGN) (2007)

Il n'y a plus de temps à perdre avant l’imposition par le gouvernement d’une centralisation massive des services de santé et des services sociaux – à quoi s'ajoute une nouvelle menace à l'accès à l'anglais - Quebec Community Groups Network (QCGN) (2023)

Huge Victory for Minority Language Rights in Quebec's Superior Court - Quebec Community Groups Network (QCGN) (2020)
Keywords: Official Language Minority Community (OLMC)

How Powers are Divided Between our Federal and Provincial Governments - Quebec Community Groups Network (QCGN) (2020)

House of Commons Committee Votes to Forsake English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2023)

Future Restrictions for Admissions to English-language CEGEPs Scruitinized - Quebec Community Groups Network (QCGN) (2022)

Future of English-speaking Quebecers is Core Element for Modernization of Official Languages Act - Quebec Community Groups Network (QCGN) (2018)

French-speaking Quebecers Strongly Support Right of English-speaking Citizens to Obtain Government Services in English – Poll - Quebec Community Groups Network (QCGN) (2022)

French Language Minister Tables Six New Amendments to Bill 96 Regarding Online Business Transactions, Commissioner Obligations, and Enforceability Contracts - Quebec Community Groups Network (QCGN) (2022)

Ferme appui des membres du QCGN à la lutte contre les lois et les politiques qui sapent les droits des Québécois d’expression anglaise - Quebec Community Groups Network (QCGN) (2022)

Federally Regulated Businesses and the New Languages Landscape - Quebec Community Groups Network (QCGN) (2021)

Federal Budget Includes New Money for Official-Language Minorities - Quebec Community Groups Network (QCGN) (2023)

Exemptions to the Use of French by Government Under Scrutiny by Committee - Quebec Community Groups Network (QCGN) (2022)

Examen par la commission des cas d’exception à l’utilisation du français par le gouvernement - Quebec Community Groups Network (QCGN) (2022)

English-speaking Seniors Unite to Create Provincial Vote - Seniors Action Quebec (2013)

English-speaking Quebecers Shows High Levels of Distrust with Coalition Avenir Québec Government - Quebec Community Groups Network (QCGN) (2019)

English-speaking Quebec and the Provincial 2018 Election - Quebec Community Groups Network (QCGN) (2018)

English-speaking Quebec and the Modernization of the Official Languages Act : Brief Submitted to the Standing Senate Committee on Official Languages Study on Canadians' Views about Modernizing the Official Language Act - Sandilands, Marion (Quebec Community Groups Network (QCGN), 2018)
The Quebec Community Groups Network (“QCGN”) welcomes this opportunity to contribute to this Committee’s study on modernizing the Official Languages Act (“the Act”). In the spirit of modernization, the QCGN takes this opportunity to present a picture of the contemporary English-speaking community of Quebec. As this Committee noted in 2011, there are certain widely-held myths regarding this community. The QCGN hopes to contribute to a modernized understanding of this community and its role as a unique and important official language minority community in Canada.
Keywords: Official Language Minority Community (OLMC)

English-speaking Community Very Concerned About Barrette Reform Bill - Quebec Community Groups Network (QCGN) (2014)

English-speaking Community Representation in Network Governance : Info sheet no.3 - Quebec Community Groups Network (QCGN)
Bill 10 adopted in February 2015, did not replace the Health and Social Services Act, often referred to as S 4.2. But it substantially changed certain of its provisions. In particular, it radically altered the way in which Quebec’s public health and social services system is administered. It changed the identity of the institutions that deliver health and social services, the composition and manner of appointment of board members, and for the first time created the possibility for at least one person coming from the English-speaking community to have a seat on each one of the 22 Centre Intégrés (CI) which now deliver all of the regionally based services. There is one CI per region where CIs exist, except Gaspé which has two, Montérégie which has three, and Montréal which has five.

English-speaking Community Needs Formal Presence in Provincial Government, says QCGN members - Quebec Community Groups Network (QCGN) (2013)

English-speaking Community Disagrees Profoundly with Government on Secularism Bill - Quebec Community Groups Network (QCGN) (2019)

English and French : Towards the Substantive Equality of Official Languages in Canada - Quebec Community Groups Network (QCGN) (2021)
The Government of Canada’s paper on official language reform captures important demands made by the English-speaking community of Quebec during consultative processes related to the modernization of the Official Languages Act. There is reason for optimism around proposals for an expanded role of Treasury Board and power of the Commissioner of Official Languages in the implementation of the Act. And there are opportunities for increased support to our community’s institutions and provisions for more transparency on federal transfers directed towards our vitality; proposals that are tempered by the need for provincial cooperation.

Educational Institutions Must Tie Their Activities to the Vitality of the Communities They Serve - Quebec Community Groups Network (QCGN) (2016)

Discours d’ouverture de la présidente du QCGN, l’honorable Marlene Jennings, C.P., LL. B. au Commission de la culture et de l'éducation : Consultations particulières et audiences publiques sur le projet de loi 96, Loi sur la langue officielle et commune du Québec, le français - Quebec Community Groups Network (QCGN) (2021)

Developing Regulations for Part VII (Advancement of Equality of Status and Use of English and French) of the Official Languages Act - Official Languages Centre of Excellence Office of the Chief Human Resources Officer (2024)

Developing an Arts, Culture and Heritage Policy Framework for English-speaking Quebec - English Language Arts Network (ELAN) (2008)
This policy describes the philosophy, principles, development guidelines, priorities and operational considerations that English-speaking Quebec intends to pursue in the coming years to develop and disseminate the its different forms of cultural expression: It includes ideas that could engage a wide variety of different organizations in pursuing the full implementation of this policy.
Keywords: Official Language Minority Community (OLMC)

Déclaration du QCGN sur le rapport du Bloc Québécois concernant le financement fédéral de la minorité d’expression anglaise du Québec - Quebec Community Groups Network (QCGN) (2023)

Déclaration du QCGN concernant le projet de loi 15 et le recours au bâillon - Quebec Community Groups Network (QCGN) (2023)

Déclaration de L’honorable Marlene Jennings, C.P. Présidente Quebec Community Groups Network concernant l’adoption du projet de loi 96 - Quebec Community Groups Network (QCGN) (2022)

Débats de la Commission sur les processus de plaintes adressées à l'office Québécois de la langue française - Quebec Community Groups Network (QCGN) (2022)

Dear Mr. Premier : English-speaking Quebecers are full-fledged, contributing members of Quebec society - Quebec Community Groups Network (QCGN) (2021)

De plus en plus de Québécois d’expression anglaise rejettent l’approche conflictuelle concernant les « anglophones historiques » - Quebec Community Groups Network (QCGN) (2022)

Dans une lettre ouverte, le QCGN demande le retrait des références à la Charte de la langue française du Québec dans le projet de loi fédérale C-13 - Quebec Community Groups Network (QCGN) (2022)

CRTC Must Oblige Vidéotron to Restore English-language Community Television Station - Quebec Community Groups Network (QCGN) (2013)

CRTC Decision on CBC License Renewal Good News for English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2013)

Croissance de l’opposition à la définition restrictive de la communauté d’expression anglaise - Quebec Community Groups Network (QCGN) (2021)

Consensus on Language Issues in Quebec - Quebec Community Groups Network (QCGN); Association for Canadian Studies (2022)

Community Leaders Ready to Assist Kathleen Weil, Quebec's New Minister Responsible for Relations with English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2017)

Community-based Process Results in Strong Watchdog Committee for English Health and Social Services - Quebec Community Groups Network (QCGN) (2018)

Committee Substantively Changes Quebec Human Rights Laws - Quebec Community Groups Network (QCGN) (2022)

Committee Examines Rules for Posting Bilingual Positions - Quebec Community Groups Network (QCGN) (2022)

Committee Examines Obligations of Professionals to Provide Documentation in French - Quebec Community Groups Network (QCGN) (2022)

Committee Examines Language Rules Governing Business and Public Education - Quebec Community Groups Network (QCGN) (2022)

Committee Examines Effects of Agency Directives on Quebec Immigrants - Quebec Community Groups Network (QCGN) (2022)

Committee Discusses Use of French Within Businesses - Quebec Community Groups Network (QCGN) (2022)

Committee Discusses Quality of French Taught to Newcomers and English-speakers - Quebec Community Groups Network (QCGN) (2022)

Committee Discusses Creation of Francisation Québec and a Ministry of the French Language - Quebec Community Groups Network (QCGN) (2022)

Committee Debates New Complaints Procedures for the Office Québécois de la langue française - Quebec Community Groups Network (QCGN) (2022)

Committee Continues to Carve Out Exceptions to Exemplary Use of the French Language - Quebec Community Groups Network (QCGN) (2022)

Committee Continues Discussions Regarding Restrictions on CEGEP Admissions - Quebec Community Groups Network (QCGN) (2022)

Committee Continues Debate on the Future of English-language CEGEPS - Quebec Community Groups Network (QCGN) (2022)

Committee Concludes Examination of Bill 96 : CAQ Enshrines Primacy of French Language and "Quebec Nation" Over Canadian and Quebec Human Rights Charters - Quebec Community Groups Network (QCGN) (2022)

Committee Closes Debate on CEGEPS and Turns to Universities - Quebec Community Groups Network (QCGN) (2022)

Committee Begins Examination of Language Restrictions Governing CEGEP Admissions - Quebec Community Groups Network (QCGN) (2022)

Committee Adopts Series of Surprise Changes Regarding Bilingualism in Quebec Judicial Appointments - Quebec Community Groups Network (QCGN) (2022)

Committee Adopts Proposed Changes to Civil Code of Quebec - Quebec Community Groups Network (QCGN) (2022)

Committee Adds New Punitive Measures to Bill 96 - Quebec Community Groups Network (QCGN) (2022)

Commissaire au Lobbyisme du Québec : Consultation des OBNL relativement à leur assujettissement aux règles d’encadrement du lobbyisme — projet de loi 56 - Quebec Community Groups Network (QCGN) (2016)
Le Quebec Community Groups Network (QCGN) est un organisme à but non lucratif constitué en société en vertu d’une loi fédérale. Il rassemble 48 organismes du secteur communautaire partout au Québec, qui servent la communauté d’expression anglaise du Québec. Le QCGN est un centre d’expertise fondée sur des données probantes, dont l’action collective est axée sur des enjeux stratégiques ayant une incidence sur le développement et la vitalité du Québec d’expression anglaise. Un certain nombre de membres du QCGN ont exprimé leur inquiétude sur les incidences du projet de loi no 56 — la Loi sur la transparence en matière de lobbyisme — sur leurs activités. Malheureusement, la voix du secteur à but non lucratif au service de notre communauté a été largement absente des consultations publiques antérieures et en cours sur la question, ce qui entraîne beaucoup de malentendus à propos de cette législation au sein des organismes d’expression anglaise.

Collective Rights and the Declining Vitality of the English-speaking Communities of Quebec : Brief to the Committee on Culture and Education with Regards to the General Consultation and Public Hearings on Bill 103, An Act to Amend the Charter of the French Language and Other Legislative Provisions - Quebec Community Groups Network (QCGN) (2010)
Our brief deals with the declining vitality of the English-speaking communities of Quebec (ESCQ) and the relative strength of the Francophone majority. The QCGN‟s goal is to demonstrate that our minority communities are not a threat to the majority, but a constituency that strengthens Quebec society. We expose the detrimental effect that Quebec's habit of emphasising an exclusionary notion of its society has on its minority population. Finally, we seek to attain official recognition of the historic and ongoing contributions our minority makes to Quebec society and achieve legal protection of minority rights and freedoms.
Keywords: Official Language Minority Community (OLMC)

Collective Rights and the Declining Vitality of the English-speaking communities of Quebec - Leith, Linda; Macleod, Roderick (2010)

Coalition Avenir Quebec’s outrageous tuition policy hurts all Quebecers - Quebec Community Groups Network (QCGN) (2023)

Closing Remarks of Kevin Shaar, Vice-President of QCGN, to QCGN Hearings on Bill 96 - Shaar, Kevin (2021)

Canada, Quebec, and Intergovernmental Agreements to Support English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2023)

Canada Must Not Abandon its Leadership on Official Languages - Quebec Community Groups Network (QCGN) (2021)

Cabinet Shuffle Blurs Roles and Could Delay Implementation of Action Plan for Official Languages - Quebec Community Groups Network (QCGN) (2018)
Keywords: Official Language Minority Community (OLMC)

Brief to the Standing Committee on Canadian Heritage: Nurturing Media Vitality in Quebec's English-speaking Minority Communities - Quebec Community Groups Network (QCGN) (2016)
English-speaking Quebecers have consistently signalled that access to information in their own language is both a need and a priority. In a world awash with English‑language information through CNN, Time magazine and Hollywood movies galore, this may appear a bit of a contradiction. But the crucial nuance is that English-speaking Quebecers need a full flow of information in their own language about their own local and regional communities. This is becoming increasingly more difficult to achieve and maintain on a consistent basis because of two elements: the francization of daily life in Quebec; and the decline and in many cases the demise of traditional community media.

Brief to the Senate Standing Committee on Official Language’s Study of Matters Relating to Minority-language Health Services - Quebec Community Groups Network (QCGN) (2023)

Brief to the Pre-Budget Consultation Chaired by Finance Minister Eric Girard - Quebec Community Groups Network (QCGN) (2023)
Sections A to C of this brief address the funding needs of Quebec’s community sector organizations, and more specifically the needs of those organizations which provide services and programs to English-speaking Quebecers. The Quebec Community Groups Network (QCGN) has long held a mandate to collect, collate, and articulate the needs of Quebec’s English-speaking community, and the work that we have done on this file in recent years has informed these sections of our brief significantly.

Brief to the National Assembly Committee on Culture and Education : Special Consultations and Public Hearings on Bill 96, an Act Respecting French, the Official and Common Language of Quebec - Quebec Community Groups Network (QCGN) (2021)
In this brief, the QCGN articulates three sets of concerns: first, Bill 96 fundamentally alters the Quebec state, which is of concern to all Quebecers. Second, Bill 96 will make it harder to do business in Quebec, which is also of concern to all Quebecers. Third, Bill 96 will have adverse impacts on the 1.1 million Quebecers who belong to the English-speaking minority. The QCGN supports the policy goal of promoting the French language in Quebec, but suggests there are other ways to achieve this goal in an inclusive manner, to the benefit of all Quebecers.

Brief to the Expert Panel on Language of Work and Service in Federally Regulated Private Businesses - Jennings, Marlene; Shaar, Kevin (Quebec Community Groups Network (QCGN), 2021)
Canada has two official languages and two official language minorities. In its recent paper on official languages, English and French: Towards a Substantive Equality of Official Languages in Canada, the Government of Canada makes a legislative proposal to increase the use of French in federally regulated private enterprises. The paper outlines specific proposals to provide rights to work and rights to services in French – but not in English – in federally regulated private businesses in Quebec and in regions with a strong Francophone presence.

Brief to the Election System Study Panel: Minority Language Educational Rights and Canada's English Linguistic Minority Communities: Looking Forward - Quebec Community Groups Network (QCGN) (2015)

Brief to the Election System Study Panel - Quebec Community Groups Network (QCGN) (2015)
For a number of years, a political discussion has been underway in Quebec regarding the management and control of the Province’s primary and secondary school systems. This discussion has been taking place within a wider governance trend of retrenching decentralized governance of public institutions; health and social services, post-secondary institutions, and economic development to name a few. The locus of civil society’s involvement in the Province’s public life has therefore been shifted from regional power bases to the central government.
Keywords: Official Language Minority Community (OLMC)

Brief to the Committee on Culture and Education : Special Consultations and Public Hearings on Bill 105, An Act to Amend the Education Act - Quebec Community Groups Network (QCGN) (2016)
The Quebec Community Groups Network (QCGN) represents forty-eight (48) English-language community groups across Quebec. QCGN recognizes that Quebec’s English public school system is a key institution of the English-speaking community of Quebec - a linguistic minority community. The management and control of these institutions is a matter of governance subject to minority language educational rights contained in the Canadian Charter of Rights and Freedoms, and Quebec’s democratic tradition, expressed in the political rights guaranteed by the Quebec Charter of Human Rights and Freedoms.
Keywords: Official Language Minority Community (OLMC)

Brief to the Committee on Culture and Education : Quebec and the Minority Language Educational Rights and Canada’s English Linguistic Minority Communities: A New Partnership - Quebec Community Groups Network (QCGN) (2016)
Voting in elections is an intrinsic right for all Quebecers. It is beyond democratic tradition for government to capriciously remove these rights without a pressing and substantial reason. Quebec’s English public school system is a key institution of the English-speaking community of Quebec, a linguistic minority community. The management and control of these institutions is a matter of governance subject to minority language educational rights contained in the Canadian Charter of Rights and Freedoms, and Quebec’s democratic tradition, expressed in the political rights guaranteed by the Quebec Charter of Human Rights and Freedoms.
Keywords: Official Language Minority Community (OLMC)

Brief to the 2024-2025 Pre-budget Consultation - Quebec Community Groups Network (QCGN) (2024)

Brief to House of Commons Standing Committee on Official Languages : Bill C-13, An Act for the Substantive Equality of Canada's Official Languages - Quebec Community Groups Network (QCGN) (2022)
The Official Languages Act is a lifeline for English-speaking Quebec. With Quebec’s Bill 96, the community needs this lifeline more than ever. But with Bill C-13, this lifeline is fraying. Founded in 1995, the Quebec Community Groups Network (“QCGN”) is a not-for-profit organization linking English-language community organizations across Quebec. The QCGN—like the community it serves—is proud to support the protection and promotion of the French language in Canada. The QCGN advocates for linguistic duality in every province and territory. The English-speaking minority in Quebec is a diverse, bilingual, and resilient community that is facing serious economic challenges—in the face of persistent myths and stereotypes. Although the English language itself is not threatened, the English-speaking community’s challenge is in maintaining the community’s vitality and survival in all regions of Quebec.
Keywords: Official Language Minority Community (OLMC)

Brief Submitted to La commission de la santé et des services sociaux de l'Assemblée nationale du Québec Concerning Bill 10, An Act to Modify the Organization of the Health and Social Services Network, in Particular by Abolishing the Regional Agencies - Quebec Community Groups Network (QCGN) (2014)

Brief Presented to the National Assembly’s Committee on Culture and Education with Regards to General Consultation and Public Hearings on Bill 14: An Act to Amend the Charter of the French Language, the Charter of Human Rights and Freedoms and Other Legislative Provisions - Quebec Community Groups Network (QCGN) (2013)
This brief was prepared by the Quebec Community Groups Network (QCGN), an incorporated not-for-profit organization that identifies, explores and addresses strategic issues affecting the development and vitality of English-speaking Quebec. The QCGN and its 41 members work cooperatively and in partnership with community stakeholders, leaders, governments and institutions, to advance the interests of our minority community.

Bill C-13 Weakens Federal Lifeline to English-speaking Quebec When it is Most Needed - Quebec Community Groups Network (QCGN) (2021)

Bill 96 - National Assembly Committee Debates "Historic Anglo" Clause - Quebec Community Groups Network (QCGN) (2022)

Bill 96 is Profoundly Flawed and Must be Withdrawn - Quebec Community Groups Network (QCGN) (2021)

Bill 96 and the Deaf : The Unintended Consequences of Legislation - Quebec Community Groups Network (QCGN) (2021)

Bill 86 Tramples on Minority Rights and Should be Scrapped - Quebec Community Groups Network (QCGN) (2016)

Bill 40 Violates Education Rights of Quebec’s English-speaking Minority Community, Superior Court Justice Rules - Quebec Community Groups Network (QCGN) (2023)

Bill 15 Petition Gathers 6400 Signatures in 16 Days - Quebec Community Groups Network (QCGN) (2023)

Bill 103 : Collective Rights and the Declining Vitality of the English-speaking Communities of Quebec - Bourhis, Richard Y.; Foucher, Pierre (Quebec Community Groups Network (QCGN), 2010)
The first part of this brief deals with the declining vitality of the English speaking communities of Quebec (ESCQ) and the strength of the dominant Québécois francophone majority in the Province. We argue that a key premise of Bill 103 is based on the erroneous notion that the French language and its speakers are threatened in the Province of Quebec. This false premise brings the current government to draft Bill 103 with regulations making it virtually impossible for Allophone and immigrant children to be approved as pupils in the publicly funded English schools of the Province. As the past Education Minister Michele Courchesne stated on June 3rd 2010 “I won’t deny that the objective (of Bill 103) is to have as few as possible (approved)”.

Bill 10's Impact on Users' and Residents' Committees : Info sheet no.10 - Quebec Community Groups Network (QCGN)
One way in which those required to utilize the services of the health and social services network administered by the province can ensure that their rights are respected, including their access to services in English, is by referring to and/or participating in a Users’ Committee or a Residents’ Committee (also know as in-patient committees). These committees may also exist in private institutions. The committees are comprised of volunteers elected by users or in-patients.

Bill 10's Impact on the Status of Public Institutions : Info sheet no.1 - Quebec Community Groups Network (QCGN)
Bill 10, adopted in February 2015, substantially changed certain provisions of Quebec’s Health and Social Service Act (S 4.2). In particular, it radically altered the way in which Quebec’s public health and social services system is administered. It had far-reaching effects on the status of the institutions that deliver health and social services, merging almost all institutions into 22 Centres Intégrés that now deliver all of the regionally based services. The only exceptions are seven highly specialized hospitals (five in Montreal, two in Quebec City), one institution that already resembled a Centre Intégré (in region 10), and five institutions that deliver services to the Cree, Inuit and Naskapi communities (located respectively in regions 18, 17 and 09).

Bill 10's Impact on the Right to Complain : Info sheet no.11 - Quebec Community Groups Network (QCGN)
Adoption of Bill 10 did not modify the complaints regime established by the Act respecting health services and social services. However, mention of the complaints regime is included in these Info sheets to remind interested readers that it exists, and can be used with respect to issues related to access to health and social services in English. The number of reported complaints on this topic is quite low. This may be because users are satisfied with access to services in English. But other information1 suggests that there is a level of dissatisfaction with respect to access to certain types of services, and in certain institutions that exists but is not manifested by official complaints.

Bill 10's Impact on the Provincial Committee on the Delivery of Services in English : Info sheet no.4 - Quebec Community Groups Network (QCGN)
The Government of Quebec has created a Provincial Committee (PC) on the delivery of health and social services in English. The committee is sometimes referred to as the Provincial Advisory Committee, but ‘Advisory’ is not part of its official title.

Bill 10's Impact on Regional Access Committees : Info sheet no.5 - Quebec Community Groups Network (QCGN)
The Government of Quebec has created Regional Access Committees on the delivery of health and social services in English. Each of Quebec’s Health Regions (two Aboriginal Health Regions excepted) is required to have a Regional Access Committee. The committees are referred to simply as Regional Committees in the legislation.

Bill 10's Impact on Institutional Property Ownership : Info sheet no.9 - Quebec Community Groups Network (QCGN)
The institutions merged under Bill 10 into a Centre Intégré (CI) were merged by amalgamation or by grouping. Under merger by amalgamation the merged institution loses its legal identity and therefore no longer exists as an institution. The new CI assumes all of the responsibilities, liabilities and assets of the merged institution, including human resources and property. Under merger by grouping, the institution keeps its legal identity and therefore continues to exist. The new CI assumes all of the responsibilities, liabilities and assets of the grouped institution, including human resources but not property. The grouped institution keeps the ownership of its property.

Bill 10's Impact on Foundations : Info sheet no.8 - Quebec Community Groups Network (QCGN)
Many public health and social service institutions have been supported in their work over the years by a foundation, often named after the institution it supports; for example, the Batshaw Youth and Family Centres Foundation, the St Mary’s Hospital Foundation, or the Jeffery Hale-Saint Brigid’s Friends’ Foundation. In the English-speaking community some of these foundations have existed for many decades and are part of the history and identity of those groups within the English-speaking community that founded them. Bill 10 did not directly change anything that affects the legal foundation or the governance of such foundations, but the consequences of Bill 10 do have direct and real impacts on the way foundations interact with the institution they support which is now merged into another, new institution with a different name.

Bill 10's Impact on Advisory Committees : Info sheet no.7 - Quebec Community Groups Network (QCGN)
Bill 10, provides for a new volunteer committee available, if requested, to each and every merged institution under the responsibility of a Centre Intégré (CI). The committee is known as an Advisory Committee for the specific merged institution. The role of an Advisory Committee is to make recommendations to the board of the CI into which the former institution was merged with respect to preservation of the cultural, historic, linguistic, and local characteristics of the merged institution. When applicable it also establishes the necessary ties with the foundation related to, and with the persons responsible for research activities in the merged institution. For more about the reorganization of health institutions see Info sheet no. 1 on Bill 10’s impact on the status of public institutions.

Bill 10's Impact on Access Programs : Info sheet no.6 - Quebec Community Groups Network (QCGN) (Quebec Community Groups Network (QCGN))
Access Programs have been part of the process of making government funded health and social services available in English in Quebec since the 1980s. Essentially an Access Program is an inventory for a given region of which services are available in English, and where they can be accessed.

Bilingualism Essential for Evolution of Our Laws and Access to Justice for English and French-speaking Minority Communities - Quebec Community Groups Network (QCGN) (2015)

Appellate Courts Hears Challenges to Bill 21 - Quebec Community Groups Network (QCGN) (2022)

Appelate Court Hears Challenges to Bill 21 - Quebec Community Groups Network (QCGN) (2022)

Analyse minutieuse des futures restrictions concernant les admissions dans les CÉGEPs de langue anglaise - Quebec Community Groups Network (QCGN) (2022)

Action Plan on Official Languages Offers Opportunities for Quebec's English Speaking Community - Quebec Community Groups Network (QCGN) (2023)
Keywords: Official Language Minority Community (OLMC)

Access to Justice in English Project : Senior Care Services in English in Quebec : Executive Summary of Final Report and Recommendations to the Ministry of Health and Social Services - Quebec Community Groups Network (QCGN) (2023)

Access to Justice in English Project : Access to the Courts of Quebec in English : Executive Summary and Recommendations - Quebec Community Groups Network (QCGN) (2023)
QCGN’s Access to Justice in English project (“the Project”) identifies and researches areas where the English-speaking community are experiencing difficulty accessing their rights, with a strong focus on community access to public services. It leverages information as a strategic resource to understand and improve access to justice in English in Quebec.

Access to Justice in English Project : Access to Quebec government websites in English : Executive Summary and Recommendations - Quebec Community Groups Network (QCGN) (2023)
QCGN’s Access to Justice in English project (“the Project”) identifies and researches areas where the English-speaking community are experiencing difficulty accessing their rights, with a strong focus on community access to public services. It leverages information as a strategic resource to understand and improve access to justice in English in Quebec.

Access to Justice in English in Quebec : Working Together to Ensure Access to Justice in English in Quebec - Quebec Community Groups Network (QCGN)

Access to Justice for Minority Populations : Focus on the English-speaking Communities of Quebec: 2000-2016 - Shohet, Linda (Quebec Community Groups Network (QCGN), 2016)
The objectives of this project are to research access to justice issues experienced by English-speaking Quebecers from their perspective, to establish metrics for measuring access to justice that fit the needs of community members, and to make recommendations to mitigate or overcome gaps and challenges for the English-speaking community of Quebec. The guiding question is: What is the lived experience for an English-speaking Quebecer in accessing legal and judicial information and services or in interacting with any of the social services that are now understood to be implicated in the broader concept of access to justice? This literature review is the first deliverable from Phase 1 of the project with an expectation that the findings will inform the second deliverable — a research plan to fill gaps in knowledge about the reality of access to justice for the anglophone population of Quebec.

A New Multi-year Official Languages Plan to Support Canada’s English Linguistic Minority Communities - Quebec Community Groups Network (QCGN) (2016)
This aim of this document is to outline the strategic priorities of the English-speaking Community of Quebec (ESCQ), and its high-level expectations from a new multi-year Official Languages Plan to support Canada’s English linguistic minority communities. Sector and regional leaders have developed their own priorities and expectations, which the strategic priorities contained hereunder support.
Keywords: Official Language Minority Community (OLMC)

A Language Rights Regime for Federally Regulated Businesses? - Quebec Community Groups Network (QCGN) (2023)